Performance Evaluation of Combined Wind-Assisted Propulsion and Organic Rankine Cycle Systems in Ships - Shibo Zhao; Kayvan Pazouki; Rosemary Norman (Journal of Marine Science and Engineering)
With the increasingly stringent regulation of ship carbon emissions by the International Maritime Organization (IMO), improving ship energy efficiency has become a key research direction in the current shipping industry. This paper proposes and evaluates a comprehensive energy-saving solution that integrates a wind-assisted propulsion system (WAPS) and an organic Rankine cycle (ORC) waste heat power generation system. By establishing an energy efficiency simulation model of a typical ocean-going cargo ship, the appropriate optimal system configuration parameters and working fluids are determined based on minimizing the total fuel consumption, and the impact of these two energy-saving technologies on fuel consumption is systematically analyzed. The simulation results show that the simultaneous use of these two energy-saving technologies can achieve the highest energy efficiency, with the maximum fuel savings of approximately 21%. This study provides a theoretical basis and engineering reference for the design of ship energy-saving systems.